Comparative Assessment of Haematological Profile, CD4 Cell and Viral Load Counts of HIV-Positive Clients Attending Aminu Kano Teaching Hospital (AKTH), Kano State, Nigeria - Rahamat I Ishaq; Aliyu Dutsinma Usman; M Bashir (UMYU Journal of Microbiology Research)
Study’s Excerpt